Association of late-gadolinium enhancement in cardiac magnetic resonance with ventricular arrhythmias and mortality in patients with non-ischemic cardiomyopathy. (3rd October 2022) - Aslam, F; Al-Sadawi, M; Tao, M; Aleem, S; Almasry, I; Singh, A; Rashba, E; Fan, R
Abstract: Background: Late-gadolinium enhancement (LGE) in cardiac magnetic resonance (CMR) is a predictor of adverse events such as cardiovascular mortality, cardiovascular related hospitalization and defibrillation shocks in patients with non-ischemic cardiomyopathy (NICM). The correlation between LGE and ventricular arrhythmia and mortality has not been completely established. Purpose: This meta-analysis assessed the relationship between LGE in CMR with ventricular arrhythmias: sustained, non-sustained and ICD therapy; and mortality in patients with NICM. Methods: Databases were queried for studies reporting the association between LGE in CMR in NICM and ventricular arrhythmias and mortality, including Ovid MEDLINE, EMBASE, Web of Science, and Google Scholar. The search was not restricted to time or publication status. The minimal follow up duration was one year. Results: A total of 46 studies and 10, 548 patients (4, 610 with LGE vs 5, 938 without LGE) were included; mean follow up was 3 years (ranging between 13 to 71 months) and mean left ventricular ejection fraction 33%. LGE in NICM was associated with increased risk of ventricular arrhythmias and sudden cardiac death (odds ratio 4.595, 95% confidence interval 3.54–5.97; P<0.01) and mortality (odds ratio 2.949, 95% confidence interval 2.285–3.806; P<0.01). Heterogeneity is low to moderate: χ 2 =82.2, df =45 (P=0.001), I 2 =45% (Figures 1, 2). Conclusions: Our results suggest that LGE is associated with increased risk of ventricular arrhythmias, sudden cardiac death and mortality in long-term follow up. These results further substantiate the need for larger prospective randomized trials using LGE to decide ICD indication regardless of EF. There are two ongoing trials testing this indication: CMR-ICD and CMR-GUIDE. Funding Acknowledgement: Type of funding sources: None.